Study of a Far Infrared Cavity at 60 μm and 100 μm IRAS Map around the Carbon-Rich AGB Star at Galactic Latitude 8.6° - Gautam, A.K.; Aryal, B. (Scientific World, 2020)
In this paper, we discussed about the dusty environment of the far infrared cavity around the AGB star located at R.A. (J2000) =01h41m 01s and Dec (J2000) = 71° 04’ 00 9, lying within far infrared loop G125+09 6 in the far infrared IRAS maps. A cavity like structure (major diameter ∼2.55pc & minor diameter ∼0.77pc) is found to lie at R.A. (J2000) = 01h46m57.2s and DEC (J2000) = 71°24’57.1”, located at a distance ∼ 220pc from the star. We studied the distribution of flux density, dust color temperature, dust mass, visual extinction in the cavity. We further studied the distribution Planck function along extension and compression, distribution of dust color temperature along square of the major and minor diameters. The dust color temperature is found to lie in the range (19.7±1.25) K to (21.1±0.55)K which shows the cavity is isolated and stable. A possible explanation of the results will be discussed.